Pengaruh Fasilitas Laboratorium terhadap Minat Belajar Mahasiswa Program Studi Ekonomi Islam UII - Mochammad Rizal Nahsrullah; Tulasmi Tulasmi; Ryan Yuniawan (EL-TARBAWI, 2020)
Educational facilities are one of the supports in improving the quality of education. One of the educational facilities deemed necessary to support education is a laboratory and one of the disciplines that requires a laboratory to support learning is Islamic Economics. The urgency of the laboratory as a means of learning is widely recognized by educational stakeholders, through regulations that have been made by many educational institutions competing to create and develop laboratories, in addition to supporting learning and facilities for students, another reason is that regulations require educational institutions to be have a laboratory. This study aims to analyze the role and influence of the laboratory of the Islamic economics study program on student interest in the Islamic economics study program. This study uses a quantitative method with data obtained through distributing questionnaires to 277 students of Islamic Economics study program. The collected data were then analyzed using linear regression method with SPSS software. The results of this study indicate that laboratory facilities have a positive and significant effect on student interest in learning. This shows that if the laboratory facilities are improved, student interest in learning will increase.